Improving Reading Comprehension Skills through the SQ4R Learning Strategy - Astiti, Ayu Dewi; Rashid, Salman; Astriyani, Serly (Journal of Multidiscipline and Collaboration Research, 2025)
This classroom action research aims to improve the reading comprehension skills of fifth-grade students at SD Negeri Sindang III Majalengka through the implementation of the Survey, Question, Read, Reflect, Recite, Review (SQ4R) strategy. The study was motivated by the low level of students’ reading comprehension skills, as only a small number of students were able to fully understand the content of the reading materials. The research was conducted in two cycles, each consisting of the stages of planning, action implementation, observation, and reflection. The subjects of the study were 17 students in the even semester of the 2024/2025 academic year. Data were collected through teacher and student activity observations, as well as reading comprehension achievement tests. The data were analyzed descriptively by calculating the percentages of activity and learning mastery. The findings revealed a significant improvement. Teacher activity increased from 78.66% (good category) in the first cycle to 99.99% (very good category) in the second cycle. Student activity rose from 69.19% (fairly good) to 93.76% (very good). Similarly, students’ learning mastery improved from 47.05% in the first cycle to 70.58% in the second cycle. Therefore, the SQ4R strategy proved to be effective in enhancing both the learning process and outcomes of reading comprehension.